Półwysep Iberyjski i Półwysep Apeniński w traktacie kosmologicznym Jana ze Stobnicy (1470–1530) - Zawadzki, Robert K. (Rome and Iberia : Inspirations and Connections throughout History, 2021)
In this chapter the author examines the representation of the Iberian and Apennine Peninsula in the astronomical and geographical treatise Introductio in Ptolemaei cosmographiam cum longitudinibus et latitudinibus regionum et civitatum celebriorum of Jan of Stobnica. These two countries provided fertile ground for the Cracow writer to articulate his ideas about the typology of Spain and Italy, their main cities and history. By examining these geographical descriptions, the author of the chapter shows how Jan of Stobnica constructed an image of the Iberian and Apennine Peninsula in keeping with the goals and context of his own work, while creating a vision of the Iberian Peninsula as a land of battles against Saracens, and a place from which transatlantic voyages had begun in order to discover the New World.